Assessing changes in social determinants of health inequalities in South Africa : a decomposition analysis - Kehinde O. Omotoso; Steven F. Koch (BMC, 2018)
Abstract Background Despite various policy interventions that have targeted reductions in socio-economic inequalities in health and health care in post-Apartheid South Africa, evidence suggests that not much has really changed. In particular, health inequalities, which are strongly linked to social determinants of health (SDH), persist. This study, thus, examines how changes in the SDH have impacted health inequalities over the last decade, the second since the end of Apartheid. Methods Data come from information collected on social determinants of health (SDH) and on health status in the 2004, 2010 and 2014 questionnaires of the South African General Household Surveys (GHSs). The health indicators considered include ill-health status and disability. Concentration indices and Oaxaca-Blinder decomposition of change in a concentration index methods were employed to unravel changes in socio-economic health inequalities and their key social drivers over the studied time period. Results The results show that inequalities in ill-health are consistently explained by socio-economic inequalities relating to employment status and provincial differences, which narrowed considerably over the studied periods. Relatedly, disability inequalities are largely explained by shrinking socio-economic inequalities relating to racial groups, educational attainment and provincial differences. Conclusion The extent of employment, location and education inequalities suggests the need for improved health care management and further delivery of education and job opportunities; greater effort in this regard is likely to be more beneficial in some way.